The role of an ophthalmologist in the Alström syndrome diagnosis - Karadžić, Jelena; Pantelic, Jelica; Kovacevic, Igor; Trenkic Bozinovic, Marija (Vojnosanitetski pregled, 2021)
Abstract Introduction. The Alström syndrome (AS) is an extremely rare autosomal recessive genetic disorder, affecting fewer than 1: 1,000,000 people globally. It is a single gene disorder due to the mutation of ALMS1 on chromosome 2 (2p13). The AS affects multiple organs and systems. Approximately 800 affected individuals have been identified worldwide so far. Some cases of the AS may go unrecognized for years as many of the clinical features develop over a longer period of time. As the nystagmus and retinitis pigmentosa are the most consistent findings, usually the first visible sign and present at the early infant period, the main aim of this article is to emphasize the importance of the ophthalmologist in establishing an adequate diagnosis of this rare syndrome. Case report. This article describes a Serbian patient with the Alström syndrome, whose diagnosis was genetically confirmed using the whole exome sequencing. Our patient was a 7-year-old obese male with symptoms of progressive visual impairment, photophobia and nystagmus diagnosed in early childhood. On admission, the bilateral visual acuity was poor, RE 0.06, LE 0.01, the intraocular pressure within range. The funduscopy showed central retinal pigmentation, thus suggesting cone-rod retinal dystrophy with “bull’s eye maculopathy”. The initial laboratory work at the time of the consultation revealed the elevated triglycerides levels and hyperinsulinemia, increased transaminases and gamma-glutamyl transpeptidase serum activity, whereas the glucose and glycated hemoglobin (HbA1C) levels were normal. The bilirubin test results were normal. Overall, the clinical manifestations were absent. The patient’s cardiac function was normal and the echocardiography did not indicate any abnormalities at the time. His sensorineural hearing was normal as well. A molecular genetic analysis was performed. Two composite heterozygous mutations were discovered within the ALMS1 gene sequence. In addition to the clinical presentation, the mutation detection confirmed the initial diagnosis of the AS. Conclusion. The Alström syndrome should be kept in mind in case of an obese child with photophobia, nystagmus and visual impairment present from early childhood. Fundus examination by an ophthalmologist may significantly help to establish the diagnosis of this rare genetic syndrome
Keywords: alstrom syndrome; diagnosis; ophthalmologists